The List of Endemic Territories for Tick-Borne Virus Encephalitis in 2017 (Эпидемиология и вакцинопрофилактика, 2018)
The List of Endemic Territories for Tick-Borne Virus Encephalitis in 2017.http://www.rospotrebnadzor.ru/deyatelnost/ epidemiological-surveillance/